Pendidikan Kesehatan Perilaku Hidup Bersih Dan Sehat Terhadap Anak dengan Pendekatan Squad Game - Metty Nurherliyany; Agis Ricky; Budi Ernawan; Iqbal Aditia; Noviar Ramdani; Wyzell Dzikri; Yoga Setiawan (Kolaborasi: Jurnal Pengabdian Masyarakat, 2023)
Introduction: Clean and Healthy Living Behavior (PHBS) is a reflection of a family's lifestyle that always pays attention to and maintains the health of all family members. All health behaviors that are carried out with awareness so that family members or families can help themselves in the health sector and can play an active role in health activities in the community are another definition of PHBS. Objective: Clean and Healthy Living Behavior Education (PHBS) in early childhood Method: The method used is lecturing while playing with a group approach. The name of the game used is a squad game consisting of several posts. The first post is a puzzle game which contains questions and challenges. The second post demonstrates the 7 steps for washing hands by stating the steps for washing hands. The third post is a puzzle game containing keywords about hand washing and hand hygiene. The last post is about the practice of washing hands with soap and running water. Result: This community service activity was carried out on May 4, 2023, at SDN 3 Gembor, involving 1 teacher, 6 facilitators, and 12 students. The facilitator will form groups and explain the six steps for washing hands while playing, using a group education approach. The first post is a puzzle game that contains questions and challenges. The second post demonstrates the 7 steps for washing hands by stating the steps for washing hands. The third post is a puzzle game containing keywords about hand washing and hand hygiene. The last post is about the practice of washing hands with soap and running water.